Analisis Korelasi antara Karakter Komponen Hasil dengan Hasil pada Beberapa Genotipe Semangka (Citrullus lanatus) - Mulyani, Prinsip Trisna; Waluyo, Budi (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2020)
Watermelon [Citrullus lanatus (Thunberg) Matsum & Nakai] is a plant that is widely cultivated and contains important nutritional compounds such as citrulline, arginine, and glutathione. In the last few years, the consumption of vegetables and fruits in Indonesia has tended to increase but cannot be fulfilled by domestic production. Yields are influenced by the character of yield components. This research aims to study the relationship between yield component traits and yield of watermelon. The study was arranged in augmented design and planting material are 75 watermelons genotypes and 3 checks varieties. The results showed that there are some characters of yield components that correlated with yields. The characters of yield components that have positive genetic correlation and positive phenotype correlation with fruit weight are stem length, number of branches, fruit stalk length, fruit length, fruit diameter, thickness of pericarp, number of seeds per plant, and weight of seeds per plant. The yield components characters that have a negative genetic correlation with fruit weight are day to flowering. The characters of yield components that have positive genetic and phenotype correlation with seed weight per plant are fruit weight, stem length, fruit length, fruit diameter, number of seeds per plant, seed length, and seed width. The Characters of yield components that have a negative genetic correlation with seed weight are day to flowering and the first female flower emerges. The characters of yield components that correlate with the yield are used as selection markers for indirect selection.